PENGARUH PENAMBAHAN FIBER LOKAL PADA PERILAKU TORSI KOLOM BETON BERTULANG PENAMPANG LINGKARAN DENGAN TULANGAN SPIRAL (THE EFFECT OF LOCAL FIBER ON THE TORSIONAL OF SPIRALLY CIRCULAR REINFORCED CONCRETE COLUMNS) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Columns are structural element, which are dominantly axially loaded. However sometimes columns are laterally loaded by shear, bending, and torsion. In order to make column have high ductility, can be added by fiber material. The aim of the research is to find the effect of local fiber on the behavior of circular torsion concrete column with spirally reinforcement. This research is held on 6 (six) columns, three of them are normal concrete columns and the others are fiber concrete columns. The circular columns have 200 mm diameter and 950 mm length. The columns are fixed on rigid floor. The ratio of longitudinal reinforcement each column is 2,08 % and ratio of spiral reinforcement 1,45 %. The local fiber is one percent, with aspect ratio (lid) 60. Every column is loaded under constant effectiv axial load 210,186 kN and cyclic torsion until failure. The result of the research shows that with 1 % local fiber the tension strength (splitting) of the fiber concrete increase up to 40,83 %, and the compression strength is almost the same as normal concrete. The strnght of spirally reinforcement are 201,62 Mpa and 163,19 rispec- tively on normal and fiber concrete. The local fiber does not influence on first crack torsion, but increas on ultimit strength of the concrete columns, and ductility of the columns by first crack is increassed 125 %, more than normal concrete columns. The first crack of normal concrete columns experiment are higher then Skew Bending and Space Truss method, 49,81 % and 15,17 % repectively. The first crack of fiberconcrete columns experiment eqaul Skew Bending method, but lower then Space Truss 25,85 %. The ultimate torsion experiment of normal concrete columns are higher then Skew Bending and Space Truss method, 20,57 % and 28,25 % respetively. Tthe ultimate torsion fiber concrete columnsexperiment are higher than Skew Bending 12,02 %, but lower then Space Truss 13,56 %. Before the first crack, the increased angle torsion linear to torsion, and so to be large and collapse. The normal concrete columns spall suddenly, but the fiber concrete columns are not. The spalling area of normal concrete column is larger than fiber concrete column. The stiffnes of fiber concrete column is higher then normal concrete column 7,3 %.